The ecological transition to auditory-verbal therapy: Mothers' and fathers' experiences with children who wear cochlear implants - Neuss, Deirdre (University of Ottawa (Canada), 2005)
The research reported in this study centred around the experience of adopting auditory-verbal therapy from the perspective of parents whose children wear cochlear implants. Although it has been asserted that family involvement is pivotal to the communication attainment of children with hearing loss, and despite the significant parental commitment required to implement auditory-verbal therapy, there have been no studies thus far that have examined the auditory-verbal process from the parents' perspective. Therefore, the major research question was: What are parents' experiences in making the transition to auditory-verbal therapy with their children who wear cochlear implants? A qualitative case study methodology, framed in Bronfenbrenner's ecological theory of human development and family systems theory guided this exploratory study. Bronfenbrenner indicates that an ecological transition occurs "whenever during the life course, a person undergoes a change in role either within the same or a different setting" (Bronfenbrenner & Crouter, 1983, p. 381). Parents whose children are diagnosed with a hearing loss and who adopt auditory-verbal therapy experience such a transition. Participants were 9 parents and 2 auditory-verbal therapists. Data collection procedures included individual interviews, observation sessions, a group discussion and a family information questionnaire. The major themes were: personal characteristics and family interactions (microsystem level of Bronfenbrenner's model); choice, compliance and support (mesosystem); support (exosystem); and accessibility and inclusion (macrosystem). This is the first time that Bronfenbrenner's model has been used as a theoretical framework for examining auditory-verbal therapy. The study revealed the importance of parent and child personality traits and their compatibility. It underlined that support from the cochlear implant team, as well as funding from the provincial Ministries assist the parents' transition. It emphasized that ease of access to technology, therapy and speaking role models, as well as inclusion in mainstream education also facilitate this transition.
Keywords: Health Sciences, Audiology.